Passion for life, passion for land and Earth: ‘Sentipensando’ horizons from geobiographies - PANEZ PINTO, Alexander (Utopía y Praxis Latinoamericana, 2024)
Starting from Carlos Walter Porto-Gonçalves' provocation to think about "geobiographies", this article seeks to capture some of the fundamental lessons learned with said master and friend. These learnings resonate with us from the different territories that constitute us. These lessons have to do with: 1) being collective from the academy, but beyond it and, 2) those who feel the passion for the Earth need to understand it in its material/biophysical dimension, in its socio-metabolic dynamics. The legacy of Carlos Walter's journey through the continent is not static. Still, movement, we conclude by raising some contemporary questions that require us to go beyond the reflections and feelings that Carlos Walter shared with us.